Auricular Acupuncture Analgesia in Thoracic Trauma: A Case Report - Georgios S. Papadopoulos; Petros Tzimas; Antonia Liarmakopoulou; Anastasios M. Petrou (Medical Association of Pharmacopuncture Institute, 2017)
We report a case of thoracic trauma (rib fractures with pneumothorax and pulmonary contusions) with severe chest pain leading to ineffective ventilation and oxygenation. The patient presented to our emergency department. The patient had chronic obstructive pulmonary disease and was completely unable to take deep breaths and clear secretions from his bronchial tree. After obtaining informed consent, we applied auricular acupuncture to ameliorate pain and hopefully improve his functional ability to cough and breathe deeply. Within a few minutes, his pain scores diminished considerably, and his ventilation and oxygenation indices improved to safe limits. Auricular acupuncture analgesia lasted for several hours. Parallel to pain reduction, hemodynamic disturbances and anxiety significantly resolved. A second treatment nearly a day later resulted in almost complete resolution of pain that lasted at least 5 days and permitted adequate ventilation, restored oxygenation, and some degree of mobilization (although restricted due to a compression fracture of a lumbar vertebra). Nonopioid and opioid analgesics were sparsely used in low doses during the entire hospitalization period. Hemodynamic alterations and anxiety also decreased, and the patient was soon ready to be discharged.